Ecological restoration activities for long-term preservation of the alpine and sub-alpine habitats in the Retezat National Park - Kiss, Imre; Alexa, Vasile (TÁJÖKOLÓGIAI LAPOK, 2015)
This paper is focusing on the mountain pines (Pinus mugo), the juniper (Juniperus communis) and the rhododendron (Rhododendron kotschyi) common habitats, the establishing the methods of maintaining or protecting of non-degraded populations, and the restoration methods of degraded populations, within the alpine habitats conservative management belonging to the Retezat National Park.. Between the natural and artificial regeneration methods applicable to restore the degraded mountain pines populations, the regeneration by plantation seems to be the only reasonable method, having in view that the natural regeneration is difficult and require long period of time. This study begins with presentation of the preservation plans of the unique natural landscape, named Retezat National Park, located in Meridional Carpathians (Romanian Southern Carpathians) and continues with the description of the natural distribution of the mountain pines (Pinus mugo) populations and their associated herbaceous and woody species in the Retezat National Park. The renaturation with mountain pines seedlings, within the case study regarding an ecological restoration in Retezat National Park, methods, remarks and predictable results are presented. Also, the study offers details concerning the ecological principles of the destroyed habitat’s artificial regeneration, such as: the planted area, seedlings, seedling production and their transportation to the planting area and effective plantation.